ARCH/GARCH Analysis: Estimating Beef Price Volatility in Indonesia - Mubarok, Atikah Fajriyah; Komalawati, Komalawati; Setiadi, Agus (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study analyses the volatility of beef prices in Indonesia, a strategic commodity that significantly impacts the welfare of producers and consumers. The sustained and erratic price fluctuations pose an economic risk to producers and threaten farmers' economic stability. ARCH / GARCH models were used to analyze daily beef price data from 10 July 2017 to 31 December 2023, obtained from the National Strategic Food Price Information Centre of Bank Indonesia. The GARCH (2,2) model is the most suitable for estimating the volatility of beef prices in Indonesia, with low and sustainable volatility in the long run. Factors that affect this volatility include feeder cattle and beef imports, exchange rates, livestock diseases, the COVID-19 pandemic, and government policies such as PPKM and PSBB during the new normal era. Important events such as Ramadan, Eid al-Fitr, Christmas, and New Year also influence price volatility of beef. This research aims to assist the government to design more effective market stabilization policies in the short, medium, and long term period. Keywords: beef, ARCH/GARCH, price volatility, fluctuation